Maltreatment-Associated Psychiatric Problems: An Example of Environmentally Triggered ESSENCE? - Helen Minnis (The Scientific World Journal)
This paper presents a new concept—maltreatment associated psychiatric problems (MAPP)—a syndrome of overlapping complex neurodevelopmental problems in children who have experienced abuse or neglect in early life. Children with MAPP are a hidden population in the community and, in clinical settings, their problems can seem overwhelming. Individual disorders associated with maltreatment are discussed as well as the overlap between these disorders and their shared environmental and genetic predisposing factors. Because of the complex and overlapping nature of MAPP, with symptoms emerging in early life, I argue that it should be considered an example of ESSENCE. Children presenting with likely MAPP should receive a comprehensive assessment, probing for symptoms of all of the ESSENCE disorders and leading to the use of evidence-based treatments where these are available.